Aerobic exercise training rescues protein quality control disruption on white skeletal muscle induced by chronic kidney disease in rats. Issue 3 (19th December 2017) - De Moraes, Wilson Max Almeida Monteiro; de Souza, Pamella Ramona Moraes; da Paixão, Nathalie Alves; de Sousa, Luís Gustavo Oliveira; Ribeiro, Daniel Araki; Marshall, Andrea G.; Prestes, Jonato; Irigoyen, Maria Claudia; Brum, Patricia Chakur; Medeiros, Alessandra
Abstract: We tested whether aerobic exercise training (AET) would modulate the skeletal muscle protein quality control (PQC) in a model of chronic kidney disease (CKD) in rats. Adult Wistar rats were evaluated in four groups: control (CS) or trained (CE), and 5/6 nephrectomy sedentary (5/6NxS) or trained (5/6NxE). Exercised rats were submitted to treadmill exercise (60 min., five times/wk for 2 months). We evaluated motor performance (tolerance to exercise on the treadmill and rotarod), cross‐sectional area (CSA), gene and protein levels related to the unfolded protein response (UPR), protein synthesis/survive and apoptosis signalling, accumulated misfolded proteins, chymotrypsin‐like proteasome activity (UPS activity), redox balance and heat‐shock protein (HSP) levels in the tibialis anterior. 5/6NxS presented a trend towards to atrophy, with a reduction in motor performance, down‐regulation of protein synthesis and up‐regulation of apoptosis signalling; increases in UPS activity, misfolded proteins, GRP78, derlin, HSP27 and HSP70 protein levels, ATF4 and GRP78 genes; and increase in oxidative damage compared to CS group. In 5/6NxE, we observed a restoration in exercise tolerance, accumulated misfolded proteins, UPS activity, protein synthesis/apoptosis signalling, derlin, HSPs protein levels as well as increase in ATF4, GRP78 genes and ATF6α protein levels accompanied by a decrease in oxidative damage and increased catalase and glutathione peroxidase activities. The results suggest a disruption of PQC in white muscle fibres of CKD rats previous to the atrophy. AET can rescue this disruption for the UPR, prevent accumulated misfolded proteins and reduce oxidative damage, HSPs protein levels and exercise tolerance.